Strategi Pengembangan Asuransi Syariah dalam Menghadapi Tantangan Pasar Global - Nabil Nasywan Ash Shiddiq; Moh Mukhsin (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
Islamic insurance is one of the Islamic financial instruments designed to provide financial protection based on sharia principles, such as mutual help (ta'awun) and risk-sharing. As a country with the largest Muslim population in the world, Indonesia has great potential to develop this industry. Over the past five years (2018-2022), the sharia insurance industry in Indonesia has shown consistent growth, reflected in an increase in gross contribution from IDR 12 trillion in 2018 to IDR 16 trillion in 2022. However, the market share of Islamic insurance remains small compared to conventional insurance, with key challenges including limited market scale, lack of product innovation, low public literacy in Islamic finance, and intense competition with conventional products. This article aims to analyze these challenges and formulate development strategies that can be implemented to strengthen the competitiveness of Islamic insurance in the global market. This research uses a qualitative approach based on secondary data analysis obtained from industry reports, scientific journals, and official publications. The results show that the main strategies for development include product innovation oriented to the needs of the global community, digitization of services to improve efficiency and accessibility, public education to increase Islamic financial literacy, strengthening regulations to create a conducive business environment, and strategic collaboration with international financial institutions to expand market networks.